Characteristics of glyme electrolytes for sodium battery: nuclear magnetic resonance and electrochemical study. (20th March 2017) - Carbone, Lorenzo; Munoz, Stephen; Gobet, Mallory; Devany, Matthew; Greenbaum, Steve; Hassoun, Jusef
Abstract: Glyme electrolytes are prepared by dissolving sodium trifluoromethane sulfonate (NaCF3 SO3 ) either in dimetoxyethane (DME) or in diethyleneglycoledimethylether (DEGDME). The solutions, designed for sodium battery applications, are thermally characterized by TGA and studied in terms of transport properties by combining pulse field gradient nuclear magnetic resonance (PFG NMR) and electrochemical techniques. Both electrolytes reveal suitable characteristics for sodium batteries, such as ion conductivity of about 10 −3 S cm −1, sodium transport number of 0.5, a stable stripping-deposition trend, and electrochemical stability windows extending from 0 to 4 V. However, the more volatile DME leads to a higher ion association degree. The suitability of both electrolytes is then verified in sodium-sulfur cells by cyclic voltammetry and galvanostatic test. The measurements confirm the reversibility of the sodium-sulfur process, and reveal the expected trend of the sulfur electrode in sodium cell with average working voltage of about 1.8 V, with a higher polarization and lower capacity for the cell using the DME-based electrolyte. Accordingly, the DEGDME-based solution appears to be more suitable for sodium battery applications.